Possibilities of Applying Multimedia Technologies in Inclusive Education - Simona Žalytė-Linkuvienė (Jaunųjų Mokslininkų Darbai, 2021)
Rapidly changing social, economic and cultural environment, the development of digital technologies, the global pandemic that broke out in 2020 and demographic challenges increase society’s need for constant change and improvement. Against the background of these challenges, the need to provide every member of society with equal opportunities for development is emphasized. This is an essential principle of inclusive education. Global and national documents emphasizing the need for inclusive education call for strengthening the ability of education to connect with all learners with behavioral, psychological, physiological or special abilities, regardless of nationality, social status, emphasis on respect for, access to and care for educational diversity, its change and growth. Inclusive education is best defined by the principles of the Good School Characteristics. Therefore, in this work, inclusive education is understood as an educational process characterized by the principles of the Good School Concept.